Motor Development of Premature Infants Born between 32 and 34 Weeks - S. A. Prins; J. S. von Lindern; S. van Dijk; F. G. A. Versteegh (Hindawi Limited, 2010)
Little is known about motor development in late preterm born infants. Our objective was to determine long-term outcome of motor skills of infants born between 32 and 34 weeks. All infants were assessed at corrected ages of 3 and 9 months, using the Alberta Infant Motor Scale. At corrected ages of 4 years, the Movement Assessment Battery for Children was done. Seventy infants were seen at 4 years of age (median of 3 assessments per infant). Abnormal assessment at 3 or 9 months of age resulted in normal outcome in almost 80% at 4 years. On the other hand, a normal outcome in the first year of life resulted in an abnormal outcome at 4 years in 10% of the infants. Our results suggest that long-term followup of these late preterm born infants is necessary, as the assessments in the first year do not predict the long-term outcome.